Thermotolerance and plasticity of camel somatic cells exposed to acute and chronic heat stress - Islam M. Saadeldin; Ayman Abdel-Aziz Swelum; Mona Elsafadi; Amer Mahmood; Aya Osama; Hassan Shikshaky; Musaad Alfayez; Abdullah N. Alowaimer; Sameh Magdeldin (Journal of Advanced Research, 2020)
The Arabian camel is the largest known mammal that can survive in severe hot climatic conditions. We provide the molecular explanation for the thermotolerance of camel granulosa somatic cells after exposure to 45 °C for 2 (acute heat shock) or 20 h (chronic heat shock). The common features of the cellular responses to acute heat stress were the increase of heat shock proteins and DNA repair enzymes expression. Actin polymerization and Rho signaling were critically activated as a cellular defense against heat shock. Cells exposed to chronic heat shock showed altered cell architecture with a decrease in total detected proteins, metabolic enzymes, and cytoskeletal protein expression. Treatment with transforming growth factor beta (TGFβ) pathway inhibitor SB-431542 suppressed the morphological alterations of cells exposed to chronic heat shock. Moreover, during the recovery stage at 38 °C for 24 h, proteomic changes were partially restored with an exponential increase in HSP70 expression, and the cells restored their normal cellular morphology on the 9th day of recovery. Full proteomics data are available via ProteomeXchange with identifier PXD012159. The strategies of cellular defense and tolerance to both thermal conditions reflect the flexible adaptability of camel somatic cells to conserve life under extremely hot conditions. Keywords: HSPs, ROCK, Actin, TGFβ, Proteomics, Camel, Anastasis